ANALGESIC AND ANTI-INFLAMMATORY PROPERTIES OF CALOTROPIS PROCERA (AINT) SALIX ALBA (International Journal of Food and Nutritional Sciences, 2022)
The analgesic and anti-inflammatory properties of methanolic extracts of Calotropis procera (Aiton) Dryand and Salix alba Linn were examined in white albino mice. Both plant extracts were evaluated for their analgesic and anti-inflammatory properties using plethysmometric assessment of formalin-induced paw edema in mice and the acetic acid writhing reaction. There was a dose-dependent analgesic effect shown by the extracts. In all tested dosages, S. alba extracts were more potent than aspirin, whereas C. procera extract demonstrated a notable reaction when compared to aspirin at doses as high as 62.5 mg/kg of plant extracts. The outcome also suggests that the extracts reduced the extent of the paw edema and shown inhibition of inflammation (*p